Fishery improvement projects: A voluntary, corporate "tool" not fit for the purpose of mitigating labour abuses and guaranteeing labour rights for workers. (January 2023) - Williams, Chris; Decker Sparks, Jessica L.
Abstract: The recent development of a Human Rights and Social Responsibility Policy for fishery improvement projects (FIPs) has accelerated industry and NGO-led initiatives to address human and labour rights violations in seafood supply chains through FIPs. However, this brief communication demonstrates that FIPs' social requirements, as currently constituted and reported, suffer from many of the same problems as other voluntary, market-based initiatives that fail to mitigate labour abuses. Examples of these shortcomings include the voluntarisation of what should be binding, international conventions and standards; moving benchmarks that lack meaning for workers; an absence of worker-defined remedy and recourse processes; and confusion around what actually constitutes a human rights due diligence process. In addition, social responsibility imperatives in FIPs present a new threat to the fight against labour abuses in supply chains in that they embrace and risk institutionalizing an ideology that moving towards, rather than complying with, fundamental human rights is acceptable.